1996
DOI: 10.1021/jm960048g
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of the Didemnins

Abstract: Bioactivities of 42 didemnin congeners, either isolated from the marine tunicates Trididemnun solidum and Aplidium albicans or prepared synthetically and semisynthetically, have been compared. The growth inhibition of various murine and human tumor cells and plaque reduction of HSV-1 and VSV grown on cultured mammalian cells were used to assess cytotoxicity and antiviral activity. Biochemical assays for macromolecular synthesis (protein, DNA, and RNA) and enzyme inhibition (dihydrofolate reductase, thymidylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
168
1
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(178 citation statements)
references
References 38 publications
6
168
1
3
Order By: Relevance
“…Aplidine inhibits endothelial cell proliferation, with an IC 50 similar to that observed for tumour cells. Other studies reported that concentrations of aplidine that completely inhibited colony formation by cancer cells were almost ineffective on bone marrow and cord blood haematopoietic progenitor cells, nonstimulated lymphocytes and hepatocytes (Sakai et al, 1996;Gomez et al, 2001;Albella et al, 2002;Erba et al, 2003;Gajate et al, 2003). In agreement, we found that the concentrations of aplidine that affected endothelial cell proliferation had no relevant antiproliferative effect on epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Aplidine inhibits endothelial cell proliferation, with an IC 50 similar to that observed for tumour cells. Other studies reported that concentrations of aplidine that completely inhibited colony formation by cancer cells were almost ineffective on bone marrow and cord blood haematopoietic progenitor cells, nonstimulated lymphocytes and hepatocytes (Sakai et al, 1996;Gomez et al, 2001;Albella et al, 2002;Erba et al, 2003;Gajate et al, 2003). In agreement, we found that the concentrations of aplidine that affected endothelial cell proliferation had no relevant antiproliferative effect on epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Aplidine, dehydrodidemnin B, is a marine-derived antitumour agent isolated from the Mediterranean tunicate Aplidium albicans (Sakai et al, 1996;da Rocha et al, 2001;Vera and Joullie, 2002). It is a cyclic depsipeptide, structurally related to other naturally occurring didemnins, such as didemnin B.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aplidine is a cyclic depsipeptide (Figure 1) structurally related to other naturally occurring didemnins. In contrast to the present candidate, those compounds are only found in various species of a Caribbean tunicate genus, Trididemnin (Sakai et al, 1996). Aplidine shows potent in vitro activity against human tumour solid cell lines, especially non-small-cell lung and colon tumour cells with IC50 values at 0.18 nM and 0.45 nm respectively (Faircloth et al, 1995;Lobo et al, 1997).…”
mentioning
confidence: 91%
“…Recently, a G 2 block was described for Aplidin in human leukaemia Molt-4 cell line (Erba et al, 2002). Inhibition of protein synthesis via GTP-dependent elongation factor 1-alpha in vitro (Crews et al, 1994), DNA and RNA syntheses in different cell lines (Crampton et al, 1984;Sakai et al, 1996) and inhibition of ornithine decarboxylase have been reported for Didemnins as well as for Aplidin (Urdiales et al, 1996;Erba et al, 2002).…”
mentioning
confidence: 99%